Fragile Gene WWOX Guides TFAP2A/TFAP2C-Dependent Actions Against Tumor Progression in Grade II Bladder Cancer - Kołat, Damian; Kałuzińska, Żaneta; Bednarek, Andrzej K.; Płuciennik, Elżbieta (Frontiers in Oncology, 2021)
Introduction: The presence of common fragile sites is associated with no-accidental chromosomal instability which occurs prior to carcinogenesis. The WWOX gene spans the second most active fragile site: FRA16D. Chromosomal breakage at this site is more common in bladder cancer patients who are tobacco smokers which suggests the importance of WWOX gene loss regarding bladder carcinogenesis. Tryptophan domains of WWOX are known to recognize motifs of other proteins such as AP-2α and AP-2γ allowing protein-protein interactions. While the roles of both AP-2 transcription factors are important for bladder carcinogenesis, their nature is different. Based on the literature, AP-2γ appears to be oncogenic, whereas AP-2α mainly exhibits tumor suppressor character. Presumably, the interaction between WWOX and both transcription factors regulates thousands of genes, hence the aim of the present study was to determine WWOX, AP-2α and AP-2γ function in modulating biological processes of bladder cancer. Methods: RT-112 cell line (grade II bladder cancer) was subjected to two stable lentiviral transductions. Overall, this resulted in six variants to investigate distinct WWOX, AP-2α or AP-2γ function as well as WWOX in collaboration with a particular transcription factor. Cellular models were examined with immunocytochemical staining and in terms of differences in biological processes using assays investigating cell viability, proliferation, apoptosis, adhesion, clonogenicity, migration, activity of metalloproteinases and 3D culture growth. Results: WWOX overexpression increased apoptosis but decreased cell viability, migration and large spatial colonies. AP-2α overexpression decreased tumor cell viability, migratory potential, matrix metalloproteinase-2 activity and clonogenicity. AP-2γ overexpression decreased matrix metalloproteinase-2 activity but increased wound healing, adhesion, clonogenicity and spatial colony formation. WWOX and AP-2α overexpression induced apoptosis but decreased cell viability, adhesion, matrix metalloproteinase-2 activity, overall number of cultured colonies and migration rate. WWOX and AP-2γ overexpression decreased tumor cell viability, proliferation potential, adhesion, clonogenicity and the ability to create spatial structures, but also increased apoptosis or migration rate. Conclusion: Co-overexpression of WWOX with AP-2α or WWOX with AP-2γ resulted in a net anti-tumor effect. However, considering this research findings and the difference between AP-2α and AP-2γ, we suggest that this similarity is due to a divergent behavior of WWOX.